Le sens ordinaire des mots comme règle d'interprétation - Lauzière, Lucie (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1987)
It is a universally adopted principle, although it may seem commonplace and virtually self-evident, that in the construction of statutes words are to be read in their "grammatical and ordinary" sense. This is essentially a fundamental rule of language based on general principles underlying human communication, which is equally fundamental to the construction of statutes. Frequently cited over the years as the golden rule of construction, the rule has undergone similar developments in common law and civil law doctrines. Today's doctrine is one of literal construction, but literal in total context. The literal meaning discloses the intention. Except in the rare cases of a mistake or omission by the legislator, the legislative intention is to be found in the entire context of the words of a statute. Incidentally, the question whether a word should be given its ordinary meaning as opposed to its special or technical meaning or its full unrestricted meaning as opposed to its restricted meaning does not constitute a departure from the literal meaning of the statute. The author discusses the notion of "grammatical and ordinary"sense and surveys how the courts have construed it over the past decades.